2021
DOI: 10.3390/ijerph182010785
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in Adults with Down Syndrome: Machine-Learning-Based Prediction of Inhibitory Capacity

Abstract: The study of executive function decline in adults with Down syndrome (DS) is important, because it supports independent functioning in real-world settings. Inhibitory control is posited to be essential for self-regulation and adaptation to daily life activities. However, cognitive domains that most predict the capacity for inhibition in adults with DS have not been identified. The aim of this study was to identify cognitive domains that predict the capacity for inhibition, using novel data-driven techniques in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…That is why a decision was made to use a tree-based iterative method—the CHAID analysis (Jojoa et al, 2021 )—complemented by a machine learning-based attributed selection, as the idea was to improve generalisation of the results obtained for these types of clinical issues in which attribute selection is of great importance. Similarly, in (Jojoa-Acosta et al, 2021 ), the sole use of machine learning methods and assessment by experts is proposed, differing from our work mainly in the recursive selection of attributes and improved with conventional statistical methods, preserving selection by experts in the field to validate outputs of the algorithms used.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…That is why a decision was made to use a tree-based iterative method—the CHAID analysis (Jojoa et al, 2021 )—complemented by a machine learning-based attributed selection, as the idea was to improve generalisation of the results obtained for these types of clinical issues in which attribute selection is of great importance. Similarly, in (Jojoa-Acosta et al, 2021 ), the sole use of machine learning methods and assessment by experts is proposed, differing from our work mainly in the recursive selection of attributes and improved with conventional statistical methods, preserving selection by experts in the field to validate outputs of the algorithms used.…”
Section: Discussionmentioning
confidence: 97%
“…The first corresponds to a classic statistical technique based on goodness of fit assessed by Chi2 distribution, while the second involves the use of machine learning techniques whose function is based on 3 different approaches: entropy, probability, and the linear ratio of the variable. Based on this, the CHAID algorithms were selected (Jojoa et al, 2021 ) for the first component, random forest (Wang et al, 2021 ), logistic regression (Qasim & Algamal, 2018 ), and support vector machine (Jojoa-Acosta et al, 2021 ) for the second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we want to emphasize that many of the serious games analyzed did not include Inhibition Capacity. We believe that it would be interesting to include this executive capacity, as some studies have indicated that Inhibition capacity is a predictive function of cognitive performance in people with ID [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A good result in executive functions in the early life stages encourages healthy social relationships in adulthood, better levels of employment, and a lower response to risky behavior [ 11 , 12 ]. Together with other cognitive functions, response inhibition is a process that aims to promote cognitive performance adjusted to one’s environment, and this is a key component in self-regulation processes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%